COVID 19 and Wage Polarization: A task based approach - Francesco Schettino; Sergio Scicchitano; Domenico Suppa (Global Labor Organization (GLO), 2024)
The aim of this paper is to estimate the effects of the COVID-19 pandemic on the wage polarization in Italy, combining individual characteristics with their task content in terms of physical proximity within the workplace. We use an innovative dataset which combines data from two sample surveys, the Italian Labor Force Survey and Italian Survey of Professions, which provides information on nature and content of the tasks. First, by employing a non-parametric method (the Relative Distribution) we detect a general increasing wage polarization in the sub-period 2020-2019, driven by lowest deciles, after a reduction in the previous one (2019-10). Different groups have been also isolated. Workers with low education, high proximity to customers job, such as the migrant, younger and female ones are the categories that more suffered the general downgrading of the Italian wages happened during the COVID-19 crisis.
Keywords: J28; J81; H12; I18; 330; Covid19; Income Polarization; Relative Distribution; Social Conflicts; Tasks